Pemberdayaan Petani Dalam Meningkatkan Kesejahteraan Masyarakat - Ardin Umar; Fahri Sibua (Peneliti.net, 2022)
Sector Agriculture is featured sector because eye livelihood part of Indonesia's population big is farmer. SP 3 is wrong one many villages cultivate plant food in the form of Chilli and Tomatoes with hope could increase scale economy and more life prosperous. Empowerment farmer in increase well-being SP 3 community is very thing urgent conducted for encourage, motivate, and strengthen potency owned economy as well as Becomes wrong one aspect independence farmer in develop activity his farm. Formulas problem study this is how empowerment farmer in increase well-being community in SP 3 District South Morotai and factors supporter and blocker what just on empowerment farmer in increase well-being community in SP 3 District South Morotai. Study this including study field ( field research ). Method processing and data analysis used in study this is quantitative data analysis with characteristic study character descriptive. Source of data used are primary data and secondary. Population in study this is whole member group farmer SP 3 District South Morotai and sample in study this i.e. 21 members group farmer. Technique data collection used is observation, interview, questionnaire and documentation. Results study show that implementation empowerment public group farmer To use increase well-being community in the farm SP 3 District South Morotai through outreach programs and training skills.